Epidemio-Clinical Aspects and MRI of Pelvic Endometriosis in Abidjan - Ndja Ange Patrick (Asian Journal of Medical Radiological Research, 2022)
Background: The objectives is to determine the epidemiological characteristics and to describe the MRI characteristics of endometriotic lesions. Subjects and Methods: This was a retrospective and descriptive study which took place in Abidjan over a period of 15 months from March 2018 to May 2019. The examinations were carried out on a high field MRI 1.5 T with the following sequences: 3 T2 plans, axial diffusion with ADC cartography, T1 FAT saturation without and with axial injection. All the data were collected from MRI reports of the patients. A total of 68 patients were selected. Epidemiological parameters (age, reason for consultation); MRI parameters (lesional semiology and location of endometriotic lesions and type of endometriosis (internal: adenomyosis and external); associated lesions) were studied. The chi-square test was used to check the relationship between some factors, the differences were considered significant whenever p was <0.05. Results: The mean age of the patients was 38.61 years with ranges of 14 and 55 years. Suspicion of endometriosis was the predominant indication in 42.65% of cases. The adenomyosis was the most frequent location with 67.65% followed by ovarian involvement (35.29%). In patients with adenomyosis, the junction area was less than 20 mm in 44.19% of them. Ovarian endometriosis was objectified in 24 patients, which is a prevalence of 35.29%. Subperitoneal endometriosis was objectified in 19.12% of cases. Among them, we noted a predominance of the involvement of the uterosacral ligaments (16.18%) followed by the involvement of the torus with 13.24% of cases. Tubal involvement was 10.29%. The association of endometriosis and fibroma was observed in 44.12% of patients. The risk of adenomyosis was high after 40 years p <0.005, ovarian localization significantly decreased with age. It was 0.07 between 30 and 40 years old and 0.03 after 40 years. Conclusion: MRI appears to be the reference imaging examination in the diagnosis and assessment of extension of pelvic endometriosis, because it offers the possibility of performing in one step a complete assessment of the compartments of the pelvis before laparoscopy. In sub-Saharan Africa and particularly in Ivory Coast, the diagnosis of endometriosis is made at an advanced age dominated by adenomyosis followed by endometriomas.